2018
DOI: 10.1108/sajbs-08-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of board characteristics on firm value: evidence from India

Abstract: Purpose The purpose of this paper is to explore the relationship of board characteristics and firm performance for Indian companies. Design/methodology/approach Corporate governance structures of 391 Indian companies out of CNX 500 companies listed on National Stock Exchange have been studied for their impact on performance of companies. Structural equation modeling methodology has been employed on data for five financial years from 2010 to 2014 for selected companies. Market-based measure (Tobin’s Q) and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
3
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 144 publications
(162 reference statements)
9
63
3
17
Order By: Relevance
“…Although much of prior studies showed frequent board meetings led to improved company performance (Al Farooque et al, 2020;Brick and Chidambaran, 2010;Mishra and Kapil, 2018;Puni and Anlesinya, 2020), the finding in the present study suggests otherwise. Board meetings are negatively associated, implying that frequent board meetings are detrimental to corporate performance.…”
Section: Findings and Analysiscontrasting
confidence: 80%
See 1 more Smart Citation
“…Although much of prior studies showed frequent board meetings led to improved company performance (Al Farooque et al, 2020;Brick and Chidambaran, 2010;Mishra and Kapil, 2018;Puni and Anlesinya, 2020), the finding in the present study suggests otherwise. Board meetings are negatively associated, implying that frequent board meetings are detrimental to corporate performance.…”
Section: Findings and Analysiscontrasting
confidence: 80%
“…Empirical evidence appears to suggest that combining the roles results in worse performance (Al Farooque et al, 2020;Chen et al, 2005;Haniffa and Hudaib, 2006;Kao et al, 2019;Shao, 2019). Mishra and Kapil (2018) found that separating the roles resulted in better corporate performance in Sri Lanka. By contrast, Jackling and Johl (2009), Ofoeda (2017) and Puni and Anlesinya (2020) observed no significant relationship between combined role and corporate performance.…”
Section: Corporate Governancementioning
confidence: 99%
“…On the contrary proponents of the resource dependency perspective advocates that directors with a greater exposure to external settings assist firms in getting better access to various key resources, which in turn improves FP (Mizruchi & Stearns, 1988). Accordingly evidence, mostly from developing markets, reports the positive influence of board size on FP (Jackling & Johl, 2009;Sheikh, Wang, & Khan, 2013;Mishra & Kapil, 2018). They have highlighted some unique characteristics of the developing market such as a large proportion of family owned firms coupled with the scarcity of qualified outside directors whereby firms tend to restrict executive positions to family members, which limits the qualified pool of human resources.…”
Section: Board Sizementioning
confidence: 99%
“…Conversely, the stewardship perspective supports role duality as it offers greater autonomy to managers who act as stewards' in maximizing shareholders wealth (Donaldson & Davis, 1991). Given the diverse theoretical view empirical findings on the issue are mixed with studies reporting positive (Sheikh et al, 2013;Azeez, 2015;Mishra & Kapil, 2018), negative (Jermias, 2007;Kao et al, 2019) and no association (Chang & Leng, 2004;Tachiwou, 2016) between role duality and FP. Nevertheless CG codes around the globe as well as in India have emphasized the separation of the role of CEO and chairman in order to limit the power of board leaders (Cadbury, 1992;SEBI, 2015).…”
Section: Role Dualitymentioning
confidence: 99%
“…On the other hand, agency theory, cited by Mishra and Kapil (2018), states that the large number of outside members of the board will make firm value go down, because they cannot align with top managers. Instead, the large number of inside supervisory board members is desired to align interests between them, so that the high firm value can be attained.…”
Section: The Effect Of Board Independence On Firm Valuementioning
confidence: 99%